PEOPLE’S PERCEPTION AND ACCEPTANCE TOWARDS HALAL PRODUCTS - Yusuf, Eddy; Yajid, Mohd Shukri Ab; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
According to Malaysia, halal can be defined as permissible or lawful. There are challenges facing by Muslim communities to determine whether the food or water that they consumed is following the concepts of halal. There are many factors that influence the customer’s intentions towards purchase, where in this study some variables have been determined to evaluate the impact and influences. While collecting variables, perceived behavior control, trust and knowledge are the elected variables that influence the intentions to purchase. To interpret the findings of such variables, different methodologies have been adopted, where regression and correlation are the major method via which relationship and effects are to be analyzed. This study enumerated some significance towards influence and relationship, where to some extent these variables do influence the purchasing intentions while they are interrelated with each other.